مهارة الاستماع في عمليةالتعليم والتعلم ووسائلها - Dian Ekawati (Institut Agama Islam Negeri (IAIN) Metro, 2017)
Arabic, is the second international language in the world, that is necessary to learn. There are four skills ini arabic taught by teachers to students in the learning process. The four skills are: listening, speaking, reading, and writting. Listening skill is the first skill obtained by students when learning Arabic. Listening skill is the skill that trains student’s skills in listening to the words and sentences of the arabic language. This skill listening, which is acquired by the students, will be used to apply in speaking and writting skills. But the accuracy in listening to the information given by the teacher will greatly affect student’s ability in conveying it (information) in either spoken or witten form. The implementation of the learning process for listening skills is inseparabel from the use of media that will be helpful in determining how smooth its learning process so that it can run properly. The appropriate use of media ini teaching listening skills will greatly affect how well the implementation of learning process is with the well inplementation of teaching listening skill, it is expected that the results of the study will also be well achieved either.